Aspectos éticos e bioéticos na comunicação de notícias difíceis por médicos residentes da clínica cirúrgica em um hospital do sul do Brasil - Souza, Danieli Brum de (2019)
The General Hospital is the place where patients requiring specialized care are admitted, either to treat acute or chronic conditions. Such conditions bring difficult news with them, being those of threat to life and personal, familiar and social well-being, due to the physical, social and emotional repercussions that may come, becoming, thus, unique experiences. Against this presupposition, ethics and bioethics present themselves as disciplines that should, in its scope of performance, guide the paths and care needed to guarantee broad rights to patients and together, a professional practice through responsibility, ethics and prudence with emphasis in human dignity. Therefore, the objective of this research was to analyze and comprehend, primarily, how the ethical and bioethical principles were known, reacted and oriented resident doctors behaviors in a team of surgical clinic, in the moment of communicating bad news to patients and relatives. The research occurred through a qualitative approach, of an exploratory and descriptive nature, starting from the thematic oral history of Meihy. Being the conceptual framework used to base this study the Principlist Theory, of Beauchamp and Childress. The data collect took place through a semi-structured interview, with 12 resident doctors of a surgical clinic, being this number attained using the saturation criterion. The data analysis occurred through content analysis proposed by Bardin. From this, resulted five categories, which are: respect to autonomy, beneficence, nonmaleficence, justice and communication in health. However, it was perceived that, in some cases, like discharges on request, the same resident doctors maintain a paternalist behavior and even omnipotence, not showing proximity to more current conduits. Through the answers that were given, limitations were noted, in the communicational process with the patient and in the work with the multiprofessional team. As far as the application of the TFIC (Term of Free and Informed Consent) goes, they considered an important document, making clear its application as a process. They reported that difficult news is a part of their daily work, however, referred not having received any specific training regarding such. They ignore protocols that help doctors to conduct and confront properly the process of unveiling diagnosis and unfavorable conduits. The authors related that difficult news aligns to the specialty of the resident doctors and that they still associate it, mainly, with cancer, death or some function loss. Such fact indicates the need for greater pedagogical investment during medical training for the purpose of developing and/or improving communicating skills. Regarding the work of the multiprofessional teams, they considered it very important, however, work more by referrals. There is little discussion among the resident doctors and the other professionals who care for the patients. It is important to highlight that the resident doctors referred emphatically their discomfort and indignation towards, mainly, the surgical cancellations, which causes, according to them, problems of clinical, psychic and ethical problems for both patients of the institution and doctors themselves and their more effective and humane performance.